ANALISIS KONTRIBUSI DAN EFEKTIVITAS SUMBER-SUMBER PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) PADA PEMERINTAH DAERAH KABUPATEN CIANJUR - Setiawan, Ade Budi; Surtini, Eneng (Jurnal Akunida, 2017)
This research aims to examine how much the effectiveness source of the local goverment income and the contribution of revenue collection at Regional Income of  Cianjur Regency, especially in the Regency of Cianjur in increasing source of local goverment income.  The unit of analisys was the Report of Income and Expenditure Budget Calculation period 2012 – 2014.  The method in this research is using descriptive methods,  with effectiveness analisys and contribution analisys as the instrument of the analisys.  The results of this research conducted shows that the average of the effectiveness of the Local Tax is 107,31 percent (very effective), Local Retribution is 105,49 percent (very effective),  Local Wealth Management is 95,54  percent (quite effective), and Other Legitimate Income is 112,51 percent (very effective).  Level of contribution of  source of local goverment income in period 2012 – 2014 strart at 0,30 percent until 10,13 percent and the result is very qiute and quite.Key word: Effectiveness, Contribution, Source of Income, Local Revenue, Local Goverment of Cianjur Regency